Determining factors the knowledge of the element of diabetic foot prevention of patients followed at the endocrinology unit of Joseph Raseta Befelatanana hospital - Razanamparany, Thierry; Raharinavalona, Sitraka A.; Raherison, Rija E.; Randrianary, Narindra C. R.; Andrianasolo, Radonirina L.; Rakotomalala, Andrianirina D. P. (International Journal of Research in Medical Sciences, 2025)
Background: Diabetic foot (DF) is a common and disabling complication of diabetes that requires effective prevention. Objectives of this study are to investigate the factors determining knowledge of preventive measures for diabetic feet. Methods: We performed a analytical, single-center, cross-sectional study at the endocrinology unit of the Joseph Raseta Befelatanana university hospital between September 2023 and January 2024. One hundred patients were included. The ANOVA test was used for the comparison of means. Chi-square was used to measure the association between two qualitative variables. The significance level of p<0.05. Results: The least known prevention elements by diabetics were: methods to remove horns (such as the use of sharp objects), those to remove nails as well as dangerous methods to warm the feet. The knowledge rates for these elements in the population were 7%, 47% and 45% respectively. Patients living in rural areas had less knowledge of podiatric prevention (p=0.03). Those with at least a "high school" level (95% CI=2.67 [1.14-6.21]; (p=0.02), diabetics with at least two dependent children (p=0.02), as well as those who followed regular treatment (p=0.03) had significantly better knowledge of these preventive measures for foot lesions. Conclusions: This study encourages a strengthening of the education of diabetics in relation to these preventive measures for foot lesions. Especially in patients with these characteristics.